Cardiovascular disease risk and associated physical activity factors in gastrointestinal cancer survivors - Su Young Kim; Hye Jung Kang; Ki-Hyun Kim; Dong Uk Kim; Seung-Joo Nam; Jae Kook Yang; Dong Kee Jang; Hyuk Soon Choi; Dae Gon Ryu; Jung Wook Lee; Jong Yoon Lee; Sohee Park; et al. (BMC, 2024)
Abstract Introduction Although the risk of CVD is increased in cancer survivors, few studies have investigated the CVD risk in survivors of gastrointestinal (GI) cancer. Therefore, we evaluated the CVD risk using the 10-year atherosclerotic cardiovascular disease (ASCVD) risk score for GI cancer survivors and associated physical activity factors. Methods Using the 2014-2019 Korean National Health and Nutrition Examination Surveys, data were collected for 262 GI cancer survivors and 1,310 cancer-free controls matched at a 1:5 ratio based on age and sex. The International Physical Activity Questionnaire Short-Form was used to assess physical activity, and the Euro QoL Questionnaire 5-Dimensional Classification (EQ-5D) was used to assess the health-related quality of life. Results A multiple logistic regression analysis demonstrated a lower risk of ASCVD in GI cancer survivors than in controls (adjusted odds ratio [aOR] = 0.73, 95% confidence interval [CI] = 0.55-0.97). Moreover, the risk of having a high ASCVD score was significantly lower in individuals who performed sufficient aerobic physical activity (aOR = 0.59, 95% CI = 0.47-0.75) and those with an EQ-5D score 1 or 2 (aOR = 0.36, 95% CI = 0.20-0.65 and aOR = 0.31, 95% CI = 0.16-0.58, respectively). Conclusions This population-based study demonstrated that engaging in sufficient physical activity can reduce the ASCVD risk among GI cancer survivors.